HUBUNGAN PERSEPSI, PAPARAN MEDIA INFORMASI DAN DUKUNGAN ORANG TUA DENGAN PRAKTIK PEMERIKSAAN PAYUDARA SENDIRI (SADARI) PADA REMAJA PUTRI DI SMA NEGERI 3 SEMARANG TAHUN 2017 - Dini Apriliyana; Farid Agusyahbana; Atik Mawarni; Djoko Nugroho (Jurnal Kesehatan Masyarakat (Undip), 2017)
Breast self-examination (BSE) is one of the early detection step that aims to determine the presence of mass in the breast. But in reality the awareness of women, especially adolescents to practice BSE is still less (25% -30%). BSE is highly recommended because about 85% of the suspected masses are symptoms of breast tumors found by the patient himself. The most cases of breast cancer is in the city of Semarang that is equal to 1255 cases (33.5%) compared with the total number of breast cancer in other districts or cities. One of the extracurricular activities in SMA Negeri 3 Semarang is the Center for Information on Adolescent Reproductive Health Counseling (PIK-KRR) and is the only school with the ongoing and most active PIK-KRR than any other equivalent school. This study aims to analyze the relationship of perception, exposure to information media and support of parents with breast self-examination practice (BSE) in adolecent girls. The type of this research is Explanatory Research with cross sectional study approach. The population is all second-years science students with  65 female students as the samples. This research applies descriptive and analytic analysis using Chi Square.The results of analysis showed that the highest percentage of girl adolescents were found in negative perception (50,8%), exposure of exposed information media (55,4%), good parent support (55,4%), and good BSE practice (55,4%). Positive perceptions of good practice (62.5%), exposure to good practice information media (61.1%) and poor support of poor practice (72.4%). The result of bivariate analysis usisng Chi Square test has no correlation between perception and  breast self-examination practice, of exposure of information media with breast self-examination practice with breast self-examination practice and has relationship to parent support (p-value = 0,0001) with  BSE practice. Thus parental support has an important role to the practice of breast self-examination rather than the perception and exposure of information media. It is recommended for schools to work together between parents and related parties to encourage teenagers to practice BSE.